Implementation of Code of Safe Working Practices for Merchant Seafarers towards Engine Crew in MV. Sultan Hasanuddin - Suyuti; Musriady; Jamaluddin; Asmayanti, St.; Rombe, Marten; Noegraha, Andi Dirga (Maritime Park: Journal of Maritime Technology and Society, 2026)
This research aimed at investigating the effectiveness of the implementation of COSWP towards the engine crew and finding out the better recommendation to increase the implementation for future needs. The research applied mixed-method research which combined between qualitative and quantitative approach. The data collected using questionnaires and an in-depth interview to engine crews at MV. Sultan Hasanuddin. Then, the data questionnaires were analyzed using SPSS and the interview data were interpreted using three steps, they were transcribing data, data reduce and data interpretation. The results of the research revealed that the mean score was 27,20 with standard deviation of 3.795. This data showed the implementation of COSWP in MV. Sultan Hasanuddin was in very effective condition. There were recommendations given by the sample of the research such as integration of COSWP to the Safety Management System (SMS) or International Safety Management (ISM) Code, training of Maritime Resource Management (MRM) and Non-Technical, internal auditory and regular evaluation, effective communication, and digital development management.